FREEDOM DOMINATION OF RABINDRANATH TAGORE’S FREEDOM POETRY: A POSTCOLONIAL APPROACH - Effendie, Haris Prasetya (NOTION: Journal of Linguistics, Literature, and Culture, 2021)
War and Independence were made by all types of imperialism movement plot. A widely place which contained natural resources, and people as the tribe was victimised to create the movement. Postcolonialism tells the wealth as freed to the motherland. The motherland or kingdom of great nationalism was called and a major attend to the nationalism day to pay the national bitter history with prayer. Kingdom of human life is wealth because the years moment has been calling human to study about political relation, nationalism relation, nationalism knowledge. Case of war and how the wealth is always in upper domination are how the poetry as a literary work to reflect the soul of cultural hope and denotation in the poetry line. Wealthy is a most appropriate statue to know the social life. The nationalism knowledge is freed because the structure of greatness what human must to study is education to speak about wealth after wealthy. Descent aspect was ordered to the identity of nation, but no less to join the political descent to restart the freedom to some nation. The wisdom from any discipline to grow and refresh the freedom identity about nature and humanity. India has the nasionalism history as Indonesia when Rabindranath Tagore also talks about how the country speak about all the day long nationally wealth in his poetry to next their life. The research was a qualitative research to apply the Postcolonialism theory.